The Cr(VI) removal from tailing wastewater by magnetic amino-functionalized sludge biochar prepared through one-pot method - Zhiping Li; Yi Zhou; Quan Yin; Lidong Ma (Desalination and Water Treatment)
Magnetic amino-functionalized sludge biochar (Fe@NBC) was prepared via a one-step method for efficient Cr(VI) removal from tailing wastewater. Static adsorption research was conducted to investigate the impacts of solution pH, coexisting ion, reaction times, pollutant concentrations, and reaction temperature on removing Cr(VI) from tailing wastewater. Spectroscopic analysis was used to research the removal mechanisms of Cr(VI). Compared with the original sludge biochar, Fe@NBC exhibited a more developed pore structure and richer reactive sites. Adsorption experiments showed that Fe@NBC achieved higher adsorption and reduction rates of Cr(VI) than BC, with faster reaction equilibrium time. The efficiencies of removing Cr(VI) on Fe@NBC decreased with increasing solution pH. The efficiencies of removing Cr(VI) by Fe@NBC decreased with increasing SO42- concentration, while Cl- and NO-3 held almost no impact on removing Cr(VI). The process of removing Cr(VI) by Fe@NBC followed pseudo-second-order kinetic model and Langmuir model. Thermodynamics suggested that Cr(VI) removal on Fe@NBC was a spontaneous and endothermic processes. The main mechanisms for Cr(VI) removal by Fe@NBC were coordination and reduction, while pore filling and electrostatic interactions played secondary roles. This work demonstrated that Fe@NBC, a magnetic amino-functionalized sludge biochar, was a highly efficient and environmentally friendly material for removing Cr(VI) from tailing wastewater.